Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/1361-6528/28/3/035302
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-driven self-organization of silver nanoparticles in 1D and 2D subwavelength gratings for plasmonic photocatalysis

Abstract: One of the main challenges in plasmonics is to conceive large-scale, low-cost techniques suitable for the fabrication of metal nanoparticle patterns showing precise spatial organization. Here, we introduce a simple method based on continuous-wave laser illumination to induce the self-organization of silver nanoparticles within high-index thin films. We show that highly regular and homogeneous nanoparticle gratings can be produced on large areas using laser-controlled self-organization processes. This very vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Hexagonal self-organisation of nanoparticles was observed by irradiating TiO2 thin films and silver nanoparticles with green CW circularly polarised light [39]. It is suggested that the mesoporous characteristic of TiO2 facilitates the movement of nanoparticles.…”
Section: Formation Of Lipss In Hexagonal Arrangementsmentioning
confidence: 99%
“…Hexagonal self-organisation of nanoparticles was observed by irradiating TiO2 thin films and silver nanoparticles with green CW circularly polarised light [39]. It is suggested that the mesoporous characteristic of TiO2 facilitates the movement of nanoparticles.…”
Section: Formation Of Lipss In Hexagonal Arrangementsmentioning
confidence: 99%
“…The mesoporous titania film is elaborated by a sol-gel process. The sol contains titanium tetraisopropoxide (TTIP, Aldrich; 97%), acetylacetone (AcAc, Aldrich; 99%), hydrochloric acid (HCl, Roth; 37%), ethanol (EtOH, Carlo Erba; absolute), Pluronic P123 ((PEO) 20 (PPO) 70 (PEO) 20 , Aldrich; MW: 5000) and de-ionized water (H 2 O) with the following molar ratios: TTIP/P123/ethanol/HCl/H 2 O/AcAc = 1:0.025:28.5:0.015:29.97:0.5. Pluronic P123 is a symmetric triblock copolymer constituted of poly(ethylene oxide)(PEO) and poly (propylene oxide) (PPO).…”
Section: Methodsmentioning
confidence: 99%
“…To solve this issue, a well-optimized laser treatment is particularly promising, namely because of the control possibilities that lasers can provide. In fact, lasers are known to be a powerful surface structuring tool [9] that can also be used for growing and tailoring the properties of nano-objects [10,11], and, particularly, for nanoparticle formation in solid matrices [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, additional possibilities related with nanoparticle presence [13,14] and with laser beam focusing in the in bulk were explored [15]. The photocontrolled organization of metallic NPs in T iO 2 and SiO 2 films was also demonstrated [12]. Additionally, self-organized nanostructures were shown to be formed by scanning CW laser irradiation [16] and even femtosecond laser pulses [17].…”
Section: Introductionmentioning
confidence: 99%